Effect Of Defense Mechanisms and Coping Strategies on Psychological Wellbeing Among University Students During the Covid-19 Pandemic - Naeem Aslam , Sumaira , A. Ahmed, Maryam, (PJE, 2023)
COVID-19 is one of the stressful and anxiety-producing events of the 20th century. Defense mechanisms and mechanisms are psychological processes that guard the individual against anxiety. This research aims to see university students' coping and defense mechanisms during the outbreak of COVID-19. Moreover, it aimed to see the effect of defense mechanisms and coping strategies on psychological well-being among university students during the COVID-19 pandemic. A sample of 300 students was taken from different universities in Pakistan. This was a cross-sectional study. Results showed that coping strategies like self-distraction, active coping, emotional support, venting, positive reframing, and religious coping were positively associated with psychological well- being while, substance use coping, behavior disengagement, self- blame coping, and venting were negatively associated with psychological wellbeing. to psychological well-being. The comparison of gender differences in defense mechanisms showed that males scored high on humor,